Modeling melanopsin‐mediated effects of light on circadian phase, melatonin suppression, and subjective sleepiness. Issue 3 (8th August 2020) - Tekieh, Tahereh; Lockley, Steven W.; Robinson, Peter A.; McCloskey, Stephen; Zobaer, M. S.; Postnova, Svetlana
Abstract: A physiologically based model of arousal dynamics is improved to incorporate the effects of the light spectrum on circadian phase resetting, melatonin suppression, and subjective sleepiness. To account for these nonvisual effects of light, melanopic irradiance replaces photopic illuminance that was used previously in the model. The dynamic circadian oscillator is revised according to the melanopic irradiance definition and tested against experimental circadian phase resetting dose‐response and phase response data. Melatonin suppression function is recalibrated against melatonin dose‐response data for monochromatic and polychromatic light sources. A new light‐dependent term is introduced into the homeostatic weight component of subjective sleepiness to represent the direct alerting effect of light; the new term responds to light change in a time‐dependent manner and is calibrated against experimental data. The model predictions are compared to a total of 14 experimental studies containing 26 data sets for 14 different spectral light profiles. The revised melanopic model shows on average 1.4 times lower prediction error for circadian phase resetting compared to the photopic‐based model, 3.2 times lower error for melatonin suppression, and 2.1 times lower error for subjective sleepiness. Overall, incorporating melanopic irradiance allowed simulation of wavelength‐dependent responses to light and could explain the majority of the observations. Moving forward, models of circadian phase resetting and the direct effects of light on alertness and sleep need to use nonvisual photoreception‐based measures of light, for example, melanopic irradiance, instead of the traditionally used illuminance based on the visual system.